The 12-Year Kwan Im Hud Couw Procession: Cultural Heritage, Community Identity, and the Dynamics of Multiculturalism in Tangerang - Jeni Harianto; Lianah; Riris Paulina Simamora; Adrallisman (Center for Research and Development of Religious Literature and Heritage, 2025)
This study examines the historical, spiritual, and social dimensions of the Kwan Im Hud Couw Procession at Boen Tek Bio Temple ritual, exploring how it has endured and adapted to modernization while preserving its essence. Employing a qualitative ethnographic approach, this research integrates participatory observation, in-depth interviews and document analysis to provide a comprehensive understanding of the procession’s evolving role. Findings of this study reveal that the ritual plays a crucial role in preserving community identity and reinforcing social solidarity. While maintaining its traditional structure, the procession has become increasingly inclusive, fostering broader participation from diverse communities. This study underscores that intangible cultural heritage can persist through community-driven innovations without compromising its traditional roots, offering valuable insights for cultural preservation policies and social integration in multicultural societies.